2017
DOI: 10.3390/catal7030092
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Transfer Hydrogenation of Biobased HMF to 2,5-Bis-(Hydroxymethyl)Furan over Ru/Co3O4

Abstract: 2,5-Bis-(hydroxymethyl)furan (BHMF) is an important biomass-based platform chemical that can be derived from the hydrogenation of biomass-based 5-hydroxymethylfurfural (HMF). In this paper, the formation of BHMF from HMF via the catalytic transfer hydrogenation (CTH) process, using isopropanol as the hydrogen source and Ru/Co 3 O 4 as the catalyst, was studied. The results revealed that the Ru/Co 3 O 4 catalyst displayed a high catalytic efficiency, and that a BHMF yield of up to 82% was obtained at 190 • C in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Wang et al [85] used Ru/Co 3 O 4 catalysts (prepared via the co-precipitation method) in the CTH of HMF to BHMF. It was found that the effect of reaction temperature and time is critical and a simplified reaction pathway from HMF to BHMF was proposed (Scheme 5).…”
Section: Furfural Derivativesmentioning
confidence: 99%
“…Wang et al [85] used Ru/Co 3 O 4 catalysts (prepared via the co-precipitation method) in the CTH of HMF to BHMF. It was found that the effect of reaction temperature and time is critical and a simplified reaction pathway from HMF to BHMF was proposed (Scheme 5).…”
Section: Furfural Derivativesmentioning
confidence: 99%
“…In this respect, the exploitation of high-efficiency catalysts is the key. For instance, Wang et al [25] and Cao et al [26] prepared two ruthenium-based catalysts, Ru/Co 3 O 4 and Ru/LDH, when they were used for the MPV reduction of HMF in isopropanol ( i PrOH), the yield of DHMF could be achieved to 82.8% and 94.0%, respectively. However, the high reaction temperature with 190 °C and 200 °C was needed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, catalytic oxidation of HMF can be converted to 2,5-diformylfuran (DFF), 2,5-furandicarboxylic acid (FDCA), 2-formyl-5-furancarboxylic acid (FFCA), and 5-hydroxymethyl-2-furancarboxylic acid (HMFCA) [14][15][16][17]. On the other hand, HMF can be hydrogenated to 2,5-bis(hydroxymethyl)-furan (BHMF), 1,6-hexanediol, 5-methylfurfural (MF), 2,5-dimethylfuran (DMF), 2,5-dimethoxytetrahydrofuran (DMTHF), and 2,5-dihydroxymethyl-tetrahydrofuran (DHMTHF) using various metals (e.g., Pt, Ru, Pd, Cu, Zr) on different supports (e.g., C, SiO 2 , Co 3 O 4 ) [17][18][19][20][21][22]. As one of promising bio-based downstream products, BHMF can be applied in the preparation of various functional materials (e.g., polymers, resins, crown ethers, and artificial fibers), and used as versatile scaffolds in the preparation of medicines and relevant bioactive compounds [23].…”
Section: Introductionmentioning
confidence: 99%
“…As one of promising bio-based downstream products, BHMF can be applied in the preparation of various functional materials (e.g., polymers, resins, crown ethers, and artificial fibers), and used as versatile scaffolds in the preparation of medicines and relevant bioactive compounds [23]. In most cases, the efficient catalytic hydrogenation of HMF into BHMF mainly occurs over precious metals (e.g., Ru, Pd) [20,24], or transition metals (e.g., Cu) [25][26][27][28] under a relatively high pressure of H2 (1-10 MPa), see Table 1. The employed metallic catalysts are typically expensive, with relatively harsh reaction conditions [20,25].…”
Section: Introductionmentioning
confidence: 99%